Vestiges of Sexism and Gender Stereotyping: ZIMSEC Ordinary Level English Language Examinations from 2007 to 2012. - Jenjekwa, Vincent; Rutoro, Ester; Runyowa, Julius (Elsevier, 2022)
The struggle against sexism and gender stereotyping in education has resulted in concerted efforts to produce teaching and learning resources which bear particular sensitivity to gender issues. One area which still needs realignment is the area of Zimbabwe Schools Examinations Council (ZIMSEC) Ordinary level English Language examinations. The paper argues that ZIMSEC Ordinary Level English Language Paper 2 examinations, in content and tone, engender the perception that the examinations are masculine, largely dwelling on masochist stories of male adventurism, as well as male intellectual and physical prowess. The paper recommends that item writers should display utmost sensitivity to issues of gender equality in their setting of examinations to ensure that any vestiges of sexism and gender stereotyping are eradicated once and for all. The research is qualitative in nature and relied exclusively on critical document study. Statistical information presented in the research was interpreted qualitatively.